PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA AL-CHASANAH JAKARTA BARAT - Mulki Muhamadsahfan (Jurnal Tarbiyah Jamiat Kheir, 2026)
Abstract In this study entitled "the effect of social media use on student learning outcomes in Islamic Religious Education (PAI) subjects at Al Chasanah Senior High School Tanjung Duren, West Jakarta". It was found that there was no significant influence on student learning outcomes in PAI subjects. This study used a quantitative correlation method. Based on the data obtained from the questionnaire results, the X variable was 66.46 <90 which means it is in the sufficient category and the Y variable result was 85.83 <90 which is categorized as good. Then the data was processed using the Pearson product moment correlation formula to see the influence between variables and obtained a score of -0.114 which is categorized as having no influence. While the results of the determination test showed that the use of social media contributed 1,30% to student learning outcomes, while the rest was influenced by other variables outside this study. The results of the significance test using the t-count formula obtained a value of -0.607. Based on these findings, it can be concluded that social media use has a -0.114<2.101 (t-table) effect with a significance level of 5%, meaning it is categorized as very low on student learning outcomes in Islamic Religious Education at Al Chasanah Senior High School, Tanjung Duren, West Jakarta. Keywords: Social Media, Learning Outcomes, Islamic Religious Education.